1992
DOI: 10.1083/jcb.119.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an E-selectin region critical for carbohydrate recognition and cell adhesion [published erratum appears in J Cell Biol 1993 Feb;120(4):1071]

Abstract: Abstract. E-selectin elicits cell adhesion by binding to the cell surface carbohydrate, sialyl Lewis X (sLex). We evaluated the effects of mutations in the E-selectin lectin domain on the binding of a panel of anti-E-selectin mAbs and on the recognition of immobilized sLe x glycolipid. Functional residues were then superimposed onto a three-dimensional model of the E-selectin lectin domain. This analysis demonstrated that the epitopes recognized by blocking mAbs map to a patch near the antiparallel beta sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(102 citation statements)
references
References 71 publications
3
96
1
2
Order By: Relevance
“…Mutation at Lys 113 completely abolishes E-selectin and P-selectin ligand-binding function, and mutation at Lys 111 severely decreases but does not abolish function (15)(16)(17). One possible model is that Lys 113 forms an ionic hydrogen bond to the sialic acid carboxylate in sLe x in all three selectins and Lys 111 forms a hydrogen bond to this carboxylate or to the nearby anomeric oxygen or C-7 hydroxyl oxygen, which perhaps is more favorable in E-selectin and P-selectin than L-selectin.…”
Section: Dynamics Of Leukocyte Rolling On Mildly Oxidized Ligands 5410mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation at Lys 113 completely abolishes E-selectin and P-selectin ligand-binding function, and mutation at Lys 111 severely decreases but does not abolish function (15)(16)(17). One possible model is that Lys 113 forms an ionic hydrogen bond to the sialic acid carboxylate in sLe x in all three selectins and Lys 111 forms a hydrogen bond to this carboxylate or to the nearby anomeric oxygen or C-7 hydroxyl oxygen, which perhaps is more favorable in E-selectin and P-selectin than L-selectin.…”
Section: Dynamics Of Leukocyte Rolling On Mildly Oxidized Ligands 5410mentioning
confidence: 99%
“…The three-dimensional structure is known for E-selectin (15). Sitedirected mutagenesis studies have identified a number of residues that are critical to P-selectin-and E-selectin-mediated carbohydrate recognition (15)(16)(17). All three selectins bind sialylated, fucosylated lactosaminoglycans, of which the prototype is sialyl Lewis x (sLe x ; Neu5Ac␣2-3Gal␤1-4(Fuc␣1-3)GlcNAc) (18,19).…”
mentioning
confidence: 99%
“…The soluble E-selectin construct consisting of only the Lec-EGF domains, 21 and the anti-E-selectin nonblocking mAb 1D6 ͑mIgG1͒, 15 were from Hoffmann-La Roche Inc. ͑Nutley, NJ͒. The P-selectin Lec-EGF construct, 28 anti-E-selectin blocking ͑ES1͒ and nonblocking ͑ES2͒ mAbs ͑both mIgG1͒, 33 as well as anti-P-selectin glycoprotein ligand 1 ͑PSGL-1͒ blocking mAb PL1 ͑mIgG1͒, 30 54 …”
Section: Selectin Constructs Antibodies and Cell Linesmentioning
confidence: 99%
“…Independent studies identified the same region in P-selectin (Erbe et al, 1993) and the corresponding region in E-selectin (Erbe et al, 1992) to be crucial for E-and P-selectin binding to immobilized glycolipids. A subsequent crystallographic analysis on the mannose-binding protein in complex with high mannose (Weis et al, 1992) has shown that a mannose residue coordinates directly to the conserved calcium and also has suggested how a fucose residue, a part of sialylated Lewis X (sLe"), may bind to this calcium in the selectins (Weis et al, 1992).…”
Section: Examples Of Comparative Model Building: P-selectinmentioning
confidence: 99%
“…The novel fold of this protein family, with its unusually high content of nonclassical secondary structure, illustrates how crucial the identification of a closely related structural template has been for model building of P-selectin. Using the mannose-binding protein as structural template, models of E-selectin (Erbe et al, 1992;Mills, 1993) and P-selectin (Erbe et al, 1993) were also derived by similar approaches.…”
Section: Examples Of Comparative Model Building: P-selectinmentioning
confidence: 99%